Pharmacokinetics of Indomethacin in Pregnancy - Rytting, Erik; Nanovskaya, Tatiana N.; Wang, Xiaoming; Vernikovskaya, Daria I.; Clark, Shannon M.; Cochran, Marlo; Abdel-Rahman, Susan M.; Venkataramanan, Raman; Caritis, Steve N.; Hankins, Gary D. V.; Ahmed, Mahmoud S. (Clinical pharmacokinetics, 2014)
Background and objectives Although indomethacin has been widely used for the treatment of preterm labor over the past 40 years, there are few reports regarding its pharmacokinetics in pregnant women. Methods This opportunistic study assessed the steady-state pharmacokinetics of indomethacin in pregnant subjects to whom an oral dose of 25 mg every 6 h was prescribed. Indomethacin concentrations in plasma and urine were analyzed by a validated high-performance liquid chromatography method with mass spectrometric detection. Results The mean area under the plasma concentration versus time curve at steady state (AUC ss ) was 1.91 ± 0.53 μg·h/mL, mean peak plasma concentration ( C max ) was 1.02 ± 0.49 μg/mL, and mean time to reach C max ( t max ) was 1.3 ± 0.7 h. The mean apparent clearance at steady state was 14.5 ± 5.5 L/h, which is higher than the apparent clearance reported in the literature for non-pregnant subjects. Indomethacin crosses the placenta; the mean fetal/maternal ratio from five sets of cord blood samples collected at delivery was 4.0 ± 1.1. Conclusions Further studies are needed to determine whether any dose adjustments are necessary as a result of the increased clearance of indomethacin during pregnancy.